Impact of vitamin D on cognitive functions in healthy individuals: A systematic review in randomized controlled clinical trials - Ana Beatriz Januário da Silva; Ana Beatriz Januário da Silva; Waleska Maria Almeida Barros; Waleska Maria Almeida Barros; Mayara Luclécia da Silva; Mayara Luclécia da Silva; José Maurício Lucas Silva; José Maurício Lucas Silva; Ana Patrícia da Silva Souza; Ana Patrícia da Silva Souza; Karollainy Gomes da Silva; Karollainy Gomes da Silva; et al. (Frontiers in Psychology, 2022)
Various functions in the central nervous system, such as growth, development, and cognition can be influenced by vitamins and minerals, which are capable of helping to maintain brain health and function throughout life. Cognition is understood as the aspects related to knowledge, learning, and understanding, as well as the ability to develop these functions. A possible association between low levels of vit D and deficit in the performance of cognitive functions in healthy humans or with some pathological condition is discussed. Because of this, the present systematic review analyzed only randomized clinical trials carried out in healthy non-athlete adults about intellectual and/or mental processes involving cognitive functions to identify whether these individuals with different levels of vit D are capable of interfering with the performance of the cognitive function. To do so, we adopted the PRISMA method criteria and registered it in the PROSPERO database. The search was performed in PubMed (MEDLINE), PsycINFO, Science Direct, Scopus, and Web of Science databases, 2,167 records were identified. The 5 most frequent cognitive domains in the selected studies were: processing speed, attention, verbal learning/memory, executive function, and general cognitive functions. We found that there are positive changes in the following domains: verbal memory and verbal working memory, learning memory, attention, executive function, and also cognitive function in general. We highlight the following suggestions for improvements that vitamin D supplementation may promote in the cognitive domains of healthy adults: a) low doses between 400 and 600 IU/d seem to be more effective when compared to doses between 2,400 and 5,000 IU/d and b) food fortification and enrichment with vit D, need further studies, as they seem to be more or as effective as synthetic supplementation. We evident that there is a need for trials that evaluate the control of vit D levels for healthy adult individuals is important, as they have the potential to minimize health problems, especially those involved in the reduction of cognitive abilities. Thus, the development of more clinical trials to obtain satisfactory answers on this topic needs to be encouraged.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier: CRD42021262413.